Integrating the SAVI Approach with YouTube Videos in Teaching Speaking: A Case Study at Senior High School - Intan Auria Pratiwi; Desi Puspitasari (Universitas Islam Negeri Palopo, 2025)
The use of technology in this era is useful, especially in teaching speaking. This study aims to describe the implementation of the SAVI (Somatic, Auditory, Visual, Intellectual) approach through YouTube videos in teaching speaking. It’s also revealing students' perceptions of the implementation of the SAVI approach in teaching speaking. This study employed a qualitative descriptive method. The data were gathered through classroom observations, questionnaires, and semi-structured interviews with teachers and students. It involved 30 students of the eleventh grade of SMAN 1 Slahung and one teacher. The data were analyzed using the Miles and Huberman model, which involves data reduction, data presentation, and verification. The results showed that the implementation of SAVI through YouTube videos gradually blended movement, hearing, implementation, and reasoning so that learning was more interactive and student-centered and facilitated comprehension before speaking practice. Students rated this approach as helpful and enjoyable. Dealing with the students’ perceptions, they said they are more motivated, actively participating, enriching vocabulary, improving pronunciation, and more confident. The auditory and visual aspects were considered the most helpful, while the somatic supported engagement and intellectually strengthened the analysis. SAVI's approach through YouTube videos helps speaking skills and can be a reference for teachers in designing more interactive and contextual learning.